Characterization of dry eye disease in a mouse model by optical coherence tomography and fluorescein staining - Messner, Alina; Fischak, Corinna; Pfister, Martin; Schuetzenberger, Kornelia; Garreis, Fabian; Paulsen, Friedrich; Stegmann, Hannes; Dos Santos, Valentin Aranha; Garhoefer, Gerhard; Schmetterer, Leopold; Werkmeister, Rene M. (Biomedical Optics Express, 2019)
A custom-built ultrahigh-resolution optical coherence tomography (UHR-OCT) system and fluorescein staining were employed tier investigation of a scopolamine induced dry eye mouse model. Acquired data was used to evaluate common and complementary findings of the two modalities. Central corneal thickness as measured by UHR-OCT increased significantly over the study period of 24 hours, from 89.0 +/- 3.57 mu m to 92.2 +/- 4.07 mu m. Both techniques were able to show corneal lesions with a large range of severity. Localized fluorescein staining was detected in 5% and diffuse staining in 45 % of cases where no epithelial damage was visible with OCT. However, OCT revealed stromal defects in 6% and endothelial defects in 18% of the cases, which could not be visualized via fluorescein staining. Thus, while fluorescein staining widely detected defects of the corneal surface in a mouse model of dry eye disease, OCT non-invasively revealed additional intimation about defect depth and involvement of particular layers. (C) 2019 Optical Society of America under the terms of the OSA Open Access Publishing Agreement
CRIS-Team WoS Importer:2019-09-20